Total Productive Maintenance Analysis Using OEE and FMEA Method at PT. XYZ Phosphoric Acid Factory - Joumil Aidil Saifuddin; Isna Nugraha; Yekti Condro Winursito (Future Science, 2022)
The smooth production process in the company is influenced by several factors, one of which is the machine. Machine maintenance is something that needs to be done by the company because it has an important role in the smooth production process. PT XYZ is a company engaged in the manufacture of fertilizers and chemicals. Phosphoric Acid Plant, production department III A, PT XYZ, in its production process, has 193 machines that are used to process phosphate rock. Based on a survey related to problems that often occur at the Phosphoric Acid Plant, it can be seen that three machines have the highest breakdown time, namely 1st Filter (Fil-2321), 1st Vacuum Pump (C-2323), and Digester (R-2302 B). From these problems, machine maintenance analysis was carried out using Total Productive Maintenance with Overall Equipment Effectiveness and Failure Mode Effect and Analysis methods.